Relationship between physical activity in urban green space and dietary patterns among obese children in Kuala Lumpur, Malaysia - Andrew, Dogara Victor; Mohd Yusof, Mohd Johari; Abu Kasim, Junainah (Universiti Putra Malaysia Press, 2020)
In the past three decades, obesity rates affecting children in Malaysia have been rising rapidly, thereby presenting a major public health concern. However, physical activity and diet patterns in green space have been seen as effective environmental components that improve the quality of life. Hence, this study would determine the obesity levels at baseline (phase 1), after 90 days (phase 2) and after 180 days (phase 3). It further aimed to investigate the association of physical activity and diet pattern with the body mass index (BMI) of the respondents. The sample consisted of 12 respondents and this experimental study utilized a questionnaire and a checklist to record the measurements of height and weight by calculating the respondents’ physical activity, daily diet, and BMI. The scores were calculated to determine the level of obesity of the respondents by using paired sample t-test and linear regression model to analyze the influence of physical activity and diet patterns on the respondents’ BMI. The findings of this study show that there was a significant decrease in the levels of BMI before and after the study as participation in moderate to vigorous physical activities and more intake of fruits and water influence the respondents’ BMI. Therefore, this study reveals that physical activity and diet patterns in urban green space can have significant impacts on BMI and also play important roles in reducing childhood obesity.